Poliwangi Jinggo Hotel reservation system as a pilot project for Teaching Factory (TEFA) - Randhi Nanang Darmawan; I Putu Sudhyana Mecha (Journal of Applied Sciences in Travel and Hospitality, 2023)
Poliwangi Jinggo Hotel is specially addressed for educational purpose which will be used as a Teaching Factory (TEFA), so in other words this hotel will go public in near future. To support the process and everything related to hotel operation, as a baby step it is necessary to create hotel management system. The system was designed using Windows-based application (Bistone Hotel Management System). Subsequently, the research and development were carried out based on waterfall model (Requirements Analysis and Definition, System and Software Design, Implementation and Unit Testing, Integration and Unit System Testing, and Operation and Maintenance). As for the evaluation, the room reservation system was measured by quantitative approach using 30 respondents. The results obtained in this study were hotel reservation system which included setting room types, room rates, facilities, room numbers, guest input, making reservations, and printing invoices/receipts for the initial process. Based on USE Questionnaire, the results showed that the percentage of usefulness  81.2%, ease of use 80.2%, ease of learning 80%, and satisfaction 76%. Therefore, it can be concluded that Poliwangi Jinggo Hotel room reservation system is feasible to use, together with some developments and operation & maintenance process.